Glial cells in the driver seat of leukodystrophy pathogenesis - Luis M. Garcia; Julia L. Hacker; Sunetra Sase; Laura Adang; Akshata Almad (Neurobiology of Disease, 2020)
Glia cells are often viewed as support cells in the central nervous system, but recent discoveries highlight their importance in physiological functions and in neurological diseases. Central to this are leukodystrophies, a group of progressive, neurogenetic disease affecting white matter pathology. In this review, we take a closer look at multiple leukodystrophies, classified based on the primary glial cell type that is affected. While white matter diseases involve oligodendrocyte and myelin loss, we discuss how astrocytes and microglia are affected and impinge on oligodendrocyte, myelin and axonal pathology. We provide an overview of the leukodystrophies covering their hallmark features, clinical phenotypes, diverse molecular pathways, and potential therapeutics for clinical trials. Glial cells are gaining momentum as cellular therapeutic targets for treatment of demyelinating diseases such as leukodystrophies, currently with no treatment options. Here, we bring the much needed attention to role of glia in leukodystrophies, an integral step towards furthering disease comprehension, understanding mechanisms and developing future therapeutics.